Nutritional, functional, and bioactive properties of african underutilized legumes - Popoola, Jacob Olagbenro; Ojuederie, Omena B.; Aworunse, Oluwadurotimi Samuel; Adelekan, Aminat; Oyelakin, Abiodun S.; Oyesola, Olusola Luke; Akinduti, Paul A.; Dahunsi, Samuel Olatunde; Adegboyega, Taofeek T.; Oranusi, Solomon U.; Ayilara, Modupe S.; Omonhinmin, Conrad A. (Frontiers in Plant Science, 2023)
Globally, legumes are vital constituents of diet and perform critical roles in maintaining well-being owing to the dense nutritional contents and functional properties of their seeds. While much emphasis has been placed on the major grain legumes over the years, the neglected and underutilized legumes (NULs) are gaining significant recognition as probable crops to alleviate malnutrition and give a boost to food security in Africa. Consumption of these underutilized legumes has been associated with several health-promoting benefits and can be utilized as functional foods due to their rich dietary fibers, vitamins, polyunsaturated fatty acids (PUFAs), proteins/essential amino acids, micro-nutrients, and bioactive compounds. Despite the plethora of nutritional benefits, the underutilized legumes have not received much research attention compared to common mainstream grain legumes, thus hindering their adoption and utilization. Consequently, research efforts toward improvement, utilization, and incorporation into African mainstream agriculture are more convincing than ever. This work reviews some selected NULs of Africa (Adzuki beans (Vigna angularis), African yam bean (Sphenostylis stenocarpa), Bambara groundnut (Vigna subterranea), Jack bean (Canavalia ensiformis), Kidney bean (Phaseolus vulgaris), Lima bean (Phaseolus lunatus), Marama bean (Tylosema esculentum), Mung bean, (Vigna radiata), Rice bean (Vigna Umbellata), and Winged bean (Psophocarpus tetragonolobus)), and their nutritional, and functional properties. Furthermore, we highlight the prospects and current challenges associated with the utilization of the NULs and discuss the strategies to facilitate their exploitation as not only sources of vital nutrients, but also their integration for the development of cheap and accessible functional foods.